Pengaruh Selebriti Endorse Dan Brand Image Terhadap Minat Beli Produk Wardah ( Studi Kasus Pada Mahasiswa FEB Unisma ) - Adji Surya Hutama; Muhammad Ridwan Basalama; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis type of research uses explanatory research (quantitative research) through a quantitative approach. The location of the research was carried out at FEB Unisma (Wardah consumer student). Data collection techniques were carried out by distributing questionnaires to all Wardah consumers at the Islamic University of Malang. The population of this research is 90 Wardah consumers at the Islamic University of Malang. Determination of the sample in this study using a saturated sampling technique. Saturated sampling technique is a sampling technique in which all members of the population are sampled. The results of this study indicate that there is a simultaneous influence of Celebrity and Brand Image Endorser Variables on Wardah product buying interest in FEB students at the Islamic University of Malang. Keyword: Interests Buy products, Selebrity Endoseser, Brand Image